Numerical Analysis of Partial Discharge With Lossy Multi-Dielectric Insulator Forming Migration-Ohmic Model - Kang, Hyemin; Kim, Yonghee; Kim, Minhee; Lee, Se-Hee (IEEE transactions on magnetics, 2025)
Partial discharge (PD) characteristics were analyzed with a lossy multi-dielectric insulator in air forming a migration-ohmic model by using a fully coupled finite element method. In high voltage direct current (HVDC) or medium voltage direct current (MVDC) systems, electric stress is constantly applied to multi-dielectric insulators resulting in the movement of space or surface charges. The concentration of surface or space charges can cause the PD problem, which degrades the breakdown strength of insulators. To consider this aging effect in dielectric insulators, conductivity in the aged dielectric material. Challenges have emerged in developing a numerical approach for analyzing the discharge behavior with this lossy dielectric material needs to be taken into account. With the difference in material properties forming a migration-ohmic model, one has usually employed Poisson's equation for charge transport area and the current continuity equation for the lossy dielectric region, respectively, to solve this model. With these different governing equations, the electric scalar potential cannot be solved uniquely. For this reason, therefore, it has been rarely reported to analyze this migration-ohmic model in discharge analysis. To remove this uncertainty of the electric scalar potential, we introduced the current continuity equation incorporating the space charge transport equations for electrons, and positive and negative ions. To validate our numerical setup, first, a unipolar charge transport analysis with the migration-ohmic model is compared with the results from the analytic solution. Then, the temporal surface charge decay is also compared with that from an experiment reported in previous literature. Finally, we conduct a quantitative analysis of the PD patterns, considering the dynamic behavior of the surface and space charge densities within the discharge region.